Surabaya tourism management in colonial period (1906-1945) - PUSPANINGRUM, ASTRID; NILZAM ALY, M.; BAYU WIJANARKO, NUGROHO; EDI SUHARNO, NOVIANTO (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT VTV was a national tourism organization formed in 1908 to promote and organize tourism activities in the Dutch East Indies, with Batavia as its headquarter. The results of the analysis explained that Surabaya was not only a tourist destination but also a tourist sender. Main tourist objects were often visited by tourists with various backgrounds such as researchers, students, officials, and government employees. The dynamics of Surabaya's tourism were heavily influenced by major events such as the Great Depression in 1930 and World War II.